2021
DOI: 10.3102/0034654321991228
|View full text |Cite
|
Sign up to set email alerts
|

Quotation Accuracy Matters: An Examination of How an Influential Meta-Analysis on Active Learning Has Been Cited

Abstract: When previous research is cited incorrectly, misinformation can infiltrate scientific discourse and undermine scholarly knowledge. One of the more damaging citation issues involves incorrectly citing article content (called quotation errors); therefore, investigating quotation accuracy is an important research endeavor. One field where quotation accuracy is needed is in the learning sciences given its impact on pedagogy. An integral article in pedagogical discussions surrounding how to teach at the college lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…These error rates fall within the ranges reported for other fields (e.g. learning sciences 26% (Martella et al, 2021), general science 25% (Smith & Cumberledge, 2020)) and seem to suggest such error rates to be relatively consistent in recent years between various academic fields.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These error rates fall within the ranges reported for other fields (e.g. learning sciences 26% (Martella et al, 2021), general science 25% (Smith & Cumberledge, 2020)) and seem to suggest such error rates to be relatively consistent in recent years between various academic fields.…”
Section: Discussionsupporting
confidence: 85%
“…Citation inaccuracies can take many forms, ranging from easily detectible bibliographic errors to more significant errors whereby important information is misinterpreted or misrepresented (Martella et al, 2021). When errors misrepresent published data, quotes, claims and/or interpretations, they are termed "quotation errors" to distinguish these from the broader group of inaccurate citations that include bibliographic and typographical errors (Martella et al, 2021;Smith & Cumberledge, 2020). The accuracy of citation practices has been assessed for a number of fields, notably in many medical fields (reviewed in Jergas & Baethge, 2015), ecology (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, they experience a feeling of significance and their basic psychological needs are further satisfied, which further strengthens self-perceptions and motivation, and so on. That is, it is a spiraling process in which experiences of satisfying needs, motivation, and constructive actions reinforce each other (Martella et al, 2021). Numerous studies have shown that there are several ways of working and treating teachers and educators that directly support the students' needs and their positive self-perceptions (Reeve et al, 2014;Ruzek et al, 2016).…”
Section: Socio-emotional Learningmentioning
confidence: 99%